Improving public services through open data: public toilets - Bichard, Jo-Anne; Knight, Gail (Proceedings of the Institution of Civil Engineers. Municipal engineer, 2012)
Everyone needs access to toilet facilities, but such provision outside the home can be hard to find. For those with common medical conditions and older people, this issue is critical for their continued independence, quality of life and wellbeing. In the UK there is no legal requirement for local authorities to provide ‘public’ toilets, nor is there a central source of information on provision, location, access and opening times. This paper presents a case study of The Great British Public Toilet Map – a web-based information service, derived from public-sector open data. The release of data held by the UK government, under open licence, could improve transparency, accountability and help to improve public services through the reuse of such data by designers, developers and public-led campaigns for more toilet provision.